PEMANFAATAN CANGKANG BUAH KARET SEBAGAI BAHAN BAKU PEMBUATAN ARANG AKTIF DENGAN AKTIVATOR SENG KLORIDA (ZnCl2) - Nur Ardiansyah; Vonny Setiaries Johan; Nur Hasnah AR (Fakultas Pertanian Universitas Riau, 2025)
Activated charcoal is charcoal that has been activated through carbonization and activation processes to produce pores and carbon that function as adsorbents. As part of the rubber plant, the fruit shells are not widely used and are therefore often categorized as waste. As a material rich in lignocellulose, rubber fruit shells have the potential to be used in the production of activated charcoal. Conceptually, the formation of activated charcoal involves two important stages, namely the carbonization process and the activation process. The activation of the material can be carried out with the help of salt compounds, including zinc chloride (ZnCl₂) as an activating agent. The focus of this study is to find the optimum concentration of ZnCl₂ in producing activated charcoal based on rubber fruit shells with quality parameters that meet the SNI No. 06-3730-1995 standard for technical activated charcoal. An experimental approach was applied in this study using a completely randomized design (CRD) that included five treatments and three replicates for each treatment. The treatment applied was a variation in the concentration of ZNCl2 activator, namely P1 (20%), P2 (25%), P3 (30%), P4 (35%), and P5 (40%). The research data were analyzed using the ANOVA statistical method. The results of the analysis showed that differences in the concentration of zinc chloride (ZnCl₂) as an activator had a significant effect on the characteristics of moisture content, ash content, volatile matter content, bound carbon, and iodine adsorption value. Activated charcoal with the best treatment was found in treatment P4 (ZnCl2 activator concentration 35%) and met the criteria of SNI No. 06-3730-1995, with a moisture content of 2.39%, ash content of 5.20%, volatile matter content of 14.53%, fixed carbon content of 77.88%, and iodine adsorption capacity of 838.85 mg/g.